DAMPAK KOMITMEN ORGANISASI, SISTEM PENGENDALIAN INTERN PEMERINTAH, AKUNTABILITAS PUBLIK, PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL - Desy Amalia Candrakusuma; Bambang Jatmiko (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
This study aims to determine the impact of organizational commitment, the internal control system of government, public accountability, participation budget and budget goal clarity on managerial performance in the local work unit Sragen. The sampling technique in this research is done by purposive sampling. The sample in this study is a structural official echelon echelon level three and level four which consisted of the secretariat/secretary, the head of the field/section, the level of the head, as well as the head subfield/subsections at SKPD Sragen totaling 104 respondents. The technique of collecting data using questionnaires. The results of this study indicate that organizational commitment, the internal control system of government and budget goal clarity positive effect on managerial performance in the local work unit. However, public accountability and participation budget does not affect the performance of managerial work unit area. Keywords: organizational commitment, internal control system of the government, public accountability, participation budget, budget goal clarity and managerial performance on skpd.